VD_FINDINFO Arrêt / 2022 / 967 vom 21. November 2022 - VD Tribunal cantonal (2022)
RETARD INJUSTIFIÉ, RÉVISIONDÉCISION, RECONSIDÉRATION, RESTITUTIONEN GÉNÉRAL | 29 al. 1 Cst., 25 al. 1 LPGA, 51 LPGA, 53 al. 1 LPGA, 53 al. 2 LPGA